2010
DOI: 10.1016/j.cbpa.2010.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic responses of Parastacus defossus and Parastacus brasiliensis (Crustacea, Decapoda, Parastacidae) to hypoxia

Abstract: The metabolic responses of two crayfish species living in different habitats, Parastacusdefossus and Parastacus brasiliensis, were analyzed after different periods of hypoxia (2.0mg O(2)/L of oxygen). In the laboratory, groups of animals were subjected to hypoxia for 1, 2, 4, and 8h. The hemolymph, hepatopancreas, muscle, and anterior and posterior gills were removed for determination of glucose, free glucose, glycogen, lactate, total proteins, total lipids, total cholesterol, arginine, and arginine phosphate.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 37 publications
3
27
0
2
Order By: Relevance
“…When available oxygen was insufficient to support aerobic respiration, crabs relied on anaerobic fermentation, which was indicated by increasing lactate levels. Several studies reported elevation in lactate with increasing duration of hypoxia in crustaceans (Albert & Ellington, 1985;da Silva-Castiglioni et al, 2010;deFur et al, 1990;Gornik et al, 2008;Hill et al, 1991;Lallier et al, 1987;Maciel et al, 2008;Spicer et al, 2002). This study demonstrates that increasing lactate levels in a hermit crab species is directly attributable to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…When available oxygen was insufficient to support aerobic respiration, crabs relied on anaerobic fermentation, which was indicated by increasing lactate levels. Several studies reported elevation in lactate with increasing duration of hypoxia in crustaceans (Albert & Ellington, 1985;da Silva-Castiglioni et al, 2010;deFur et al, 1990;Gornik et al, 2008;Hill et al, 1991;Lallier et al, 1987;Maciel et al, 2008;Spicer et al, 2002). This study demonstrates that increasing lactate levels in a hermit crab species is directly attributable to hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous work has shown that aerial exposure can bring an internal hypoxia to this aquatic crab. Hypoxia has been reported to be an abiotic factor leading to various responses in animals such as the recourse to fermentation pathway to ensure energy homeostasis, and metabolic depression to reduce ATP consumption (Holman and Hand, 2009;da Silva-Castiglioni et al, 2010;Geihs et al, 2013;Hardy et al, 2013). In this aspect, there is surprisingly scanty information on P. trituberculatus, though many studies concerning this species have been conducted.…”
Section: Introductionmentioning
confidence: 97%
“…However, there is no consensus regarding the degree of association with burrows of each species. In Parastacus Huxley 1879, the largest and most widespread genus in South America, Noro and Buckup (2010) considered all species to be primary burrowers, whereas Silva-Castiglioni et al (2010, 2011 made a clear distinction between the life habits of Parastacus brasiliensis (von Martens, 1869) and Parastacus defossus Faxon 1898. In addition to this contradictory evidence, none of those studies actually investigated their behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we studied the behavior of P. brasiliensis; this species is considered the most 'lotic' of the genus, being more often associated with low-order streams than wetlands, although it can also live in marshlands (Buckup and Rossi 1980;Fries 1984;Buckup , 2003Silva-Castiglioni et al 2010, 2011. This is also the species of Parastacus with particularly uncertain burrowing habit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation